Survival of pathogenic and lactobacilli species of fermented olives during simulated human digestion - Arroyo-López, Francisco N.; Blanquet-Diot, Stéphanie; Denis, Sylvain; Thévenot, Jonathan; Chalancon, Sandrine; Alric, Monique; Rodríguez-Gómez, Francisco; Romero-Gil, Verónica; Jiménez-Díaz, Rufino; Garrido-Fernández, Antonio (Frontiers in Microbiology, 2014)
The present survey uses a dynamic gastric and small intestinal model to assess the survival of one pathogenic (Escherichia coli O157:H7 EDL 933) and three lactobacilli bacteria with probiotic potential (Lactobacillus rhamnosus GG, Lactobacillus pentosus TOMC-LAB2 and Lactobacillus pentosus TOMC-LAB4) during their passage through the human gastrointestinal tract using fermented olives as the food matrix. The data showed that the survival of the E. coli strain in the stomach and duodenum was very low, while its transit through the distal parts (jejunum and ileum) resulted in an increase in the pathogen population. The production of Shiga toxins by this enterohemorrhagic microorganism in the ileal effluents of the in vitro system was too low to be detected by ELISA assays. On the contrary, the three lactobacilli species assayed showed a considerable resistance to the gastric digestion, but not to the intestinal one, which affected their survival, and was especially evident in the case of both L. pentosus strains. In spite of this, high population levels for all assayed microorganisms were recovered at the end of the gastrointestinal passage. The results obtained in the present study show the potential use of table olives as a vehicle of beneficial microorganisms to the human body, as well as the need for good hygienic practices on the part of olive manufacturers in order to avoid the possibility of contamination by food-borne pathogens.